2023
DOI: 10.3389/fpubh.2023.1149872
|View full text |Cite
|
Sign up to set email alerts
|

Internet use and depressive symptoms among Chinese older adults: Two sides of internet use

Abstract: ObjectiveTo explore the relationship between internet use which includes time spent on the internet, internet skills, types of online activities, and depressive symptoms in older adults.MethodsWe used 2020 China Family Panel Studies (CFPS) data with 3,171 older adults aged 60 years. Depression symptoms were measured with the Center for Epidemiologic Studies Depression (CES-D), and internet use was measured by time spent on the internet, internet skills, and types of online activities. Multiple linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Previous studies also supported that excessive time spent on the internet had a high risk of depressive symptoms. [47] In addition, there was a large proportion population with lower educational attainment in developing countries, who contributed to less help from the internet. In particular, our study has shown that the low educational level and high rate of internet use existed simultaneously in Mexico, which explained the protective effect of internet use was minimal compared to other cohorts to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also supported that excessive time spent on the internet had a high risk of depressive symptoms. [47] In addition, there was a large proportion population with lower educational attainment in developing countries, who contributed to less help from the internet. In particular, our study has shown that the low educational level and high rate of internet use existed simultaneously in Mexico, which explained the protective effect of internet use was minimal compared to other cohorts to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Second, previous studies would suggest that the impact of Internet use on mental health should be examined in terms of the purpose of Internet use, time spent on the Internet, and Internet skills: Frequent Internet users or those who used the Internet for communication purposes received a beneficial impact on their mental health, but Internet use for health-related information searching was associated with poor mental health [ 18 , 37 ]. Prevalence of depression was higher in older adults with longer time spent on the Internet, and lower in those with higher Internet skills and in those who used the WeChat function [ 36 ]. Future research should evaluate the associations of these factors with incident disability.…”
Section: Discussionmentioning
confidence: 99%
“…The independent variables were Internet use (“Do you use the Internet?”; 1 = yes, 0 = no), length of Internet use (“How long do you use the Internet every day?”; 1 = less than 1 h, 2 = 1–3 h, 3 = 3–5 h, 4 = more than 5 h), and content of Internet use. Content of Internet use included contacting relatives and friends, watching the news, watching videos, getting health codes (a QR code used to provide personal health information during the epidemic prevention and control period), searching for health information, online payment, online shopping, playing games, and managing money ( 27 , 32 , 35 ). In addition, we collected the following characteristics of the respondents as control variables: gender (1 = male, 2 = female), age (1 = under 60 years old, 2 = 60 years old and above), marital status (1 = not married, 2 = married), residence (1 = rural, 2 = urban), education level (1 = primary school and below, 2 = junior high school, 3 = senior high school and above), employment status (1 = inactive, 2 = active).…”
Section: Methodsmentioning
confidence: 99%